Effects of wax on CH4 hydrate formation and agglomeration in oil–water emulsions. (15th August 2022) - Liu, Jia; Wang, Jing; Dong, Ti; Liang, Deqing
Graphical abstract: Highlights: Effects are investigated on the time-series of wax crystals precipitation and hydrate formation for hydrate formation and agglomeration. Wax crystals inhibit hydrate formation and reduce the aggregation of hydrate particles. Waxes affect the microscopic characteristics of hydrate crystals. Abstract: The solid sediments, resulted from hydrate formation and wax crystallization in crude oil, may generate catastrophic blockage in the pipeline under adverse conditions; this poses a formidable threat to the transportation of deep-sea crude oil. To shed light on the mechanism of the effects of waxes and hydrates in deep-sea crude oil under coexisting conditions, this work systematically investigates the effects of wax crystal precipitation and hydrate formation time-series on hydrate nucleation, growth, aggregation, and crystal structure in oil–water emulsions through experiments. Research results demonstrate that the time sequence of wax crystal precipitation and hydrate formation is concerned with the possibility of significant solid deposit formation; when wax crystal precipitation precedes hydrate formation, the wax crystals inhibit hydrate nucleation and growth; conversely, when hydrate formation precedes wax crystal precipitation, the wax significantly reduces hydrate particle aggregation, which in turn improves the flow characteristics of the hydrate slurry. Additionally, the microscopic analysis further reveals that the presence of wax has no effect on the crystal structure of CH4 hydrate, yet it has a significant effect on the distribution of CH4 in the cavities, i.e. it reduces the occupancy of large cages.